Janus kinase inhibition in the treatment and prevention of graft-versus-host disease - De Togni, Elisa; Cole, Oladipo; Abboud, Ramzi (Frontiers in Immunology, 2024)
Graft-versus-host disease (GVHD) is a significant cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). For many years, corticosteroids have been the mainstay treatment for GVHD, but cases of steroid-refractory GVHD and the severe adverse effects of high-dose corticosteroids have increased the need for preventative and therapeutic strategies for GVHD. Due to the nature of alloreactive T cells, GVHD is inherently linked to the graft-versus-leukemia (GVL) effect, the therapeutic driving force behind stem cell transplantation. A considerable clinical challenge is to preserve GVL while suppressing GVHD. The field of GVHD research has greatly expanded over the past decades, including advancements in T cell modulation and depletion, antibody therapies, chemotherapeutics, cellular therapies, and Janus kinase inhibition. In this review, we discuss current approaches and advances in the prophylaxis and treatment of GVHD with a focus on new emerging advancements in Janus kinase inhibitor therapy.